Acceptance and usage of webcasting among users of selected cyber cafes in Klang Valley - Tengku Mohd Azzman Shariffadeen, Tengku Siti Aisha; Abu Hassan, Musa; Hassan, Md. Salleh (School of Media and Communication Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2008)
The Malaysian public now has access to the Internet not only at home and the workplace, but also at cyber cafés. This study aims to examine the level of acceptance of webcasting among users of selected cyber cafés in the Klang Valley. The specific objectives of the study are: to determine the profile of webcasting users and its usage; to determine the types of webcasting technology most frequently used, level of knowledge of webcasting and the main source of knowledge in becoming aware of webcasting; to determine the acceptance of webcasting among non-users of webcasting; and to determine the relationship between behavioral intention to use and the actual usage of webcasting among users of webcasting. This study used the survey design, using purposive sampling to select the cyber cafés and visitors of these cafés. The findings indicate that usage of webcasting is still relatively low among users of selected cyber cafés in the Klang Valley. Users of webcasting were found to be mostly male, young and relatively well educated with at least a diploma as the highest level of education obtained.